The Challenges of Treating Cluster Headache in Peripheral Hospital - Sharfina, Sharfina; Irfana, Laily; Paramitasari, Aprilia (Universitas Muhammadiyah Semarang, 2021)
Cluster headache is trigeminal autonomic cephalgia with unique pain characteristics with periodicity and autonomic symptoms. Cluster headaches are rare headaches with a higher ratio in males than females. We report a case of cluster headache, a 27-year-old male patient who came in very restless and complained of shortness of breath and severe pain felt on the left side of the face, left ear, left forehead, left eye twitching, blurred vision, and it is challenging to blink, the mouth and left jaw and left nose feel stuffy. On radiological and complete blood count examination did not become the primary support for establishing the diagnosis. Enforcement of the diagnosis and proper treatment comprehensively dramatically affects the patient's prognosis, especially in modifying lifestyle and avoiding triggers of attacks.